Medical students’ attitudes toward sleeping pill usage: A cross-sectional study - Alasmari, Moudi M.; Alkanani, Raghad S.; Alshareef, Asmaa S.; Alsulmi, Shahd S.; Althegfi, Reuof I.; Bokhari, Teef A.; Alsheikh, Mona Y.; Alshaeri, Heba K. (Frontiers in Psychiatry, 2022)
Medical students experience significant stress, which may interfere with their sleeping routines; consequently, they are at a higher risk of misusing sleeping pills. Therefore, this cross-sectional convenience sampling study aims to evaluate medical students’ attitudes toward the usage of sleeping pills, as well as the prevalence of their misuse and the associated factors. A self-administered online questionnaire survey was completed by 338 medical students at the College of Medicine of the King Saud bin Abdulaziz University for Health Sciences. Of 338 participants, 84 (24.85%) reported using sleeping pills. The prevalence of sleeping pill misuse was 26.63% (n = 90). The most common misuse behavior of sleeping pills was self-prescription (n = 72, 21.30%). The factors associated with sleeping pill misuse were stimulants usage (n = 69, 92%, p = 0.0072) , high grade point average (n = 63, 84%, p = 0.046), preclinical years (n = 52, 69.3%, p = 0.042), and longer average time required to fall asleep (n = 53, 70.7%, p = 0.008). The prevalence of sleeping pill misuse is high among medical students, particularly among those in preclinical years. Therefore, enhancing awareness regarding sleeping pill misuse is crucial. This can be achieved through campaigns, workshops, and providing information regarding the dangers of sleeping pill misuse in the curriculum.